2017
DOI: 10.3390/f8070227
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Age Classes of a Pinus sylvestris (L.) Population from the Białowieża Primeval Forest, Poland

Abstract: The Białowieża Primeval Forest (BPF) is Europe's last primeval forest and an irreplaceable area for biodiversity conservation due to its size, protection status, and substantially undisturbed nature. There is no other forest in Europe with such a large surface representing highly-advanced natural succession. This article reports on the first analysis of the genetic variability and demographic structure of a self-renewed Pinus sylvestris population located in BPF, using both chloroplast and mitochondrial DNA ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Similar results were obtained in studies of natural regeneration of Scots pine [30,31] and Norway spruce [31] growing in forest understory. Higher genetic diversity in progenies of various tree species has also been found in other studies [19,20], yet this diversity tended to decrease over time probably because of natural selection [35][36][37]. The regenerating Scots pine seedlings retained the same (Swedish study by Yazdani et al [30]) or a slightly increased level of expected heterozygosity (Polish study by Nowakowska et al [31]) as compared to maternal trees.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar results were obtained in studies of natural regeneration of Scots pine [30,31] and Norway spruce [31] growing in forest understory. Higher genetic diversity in progenies of various tree species has also been found in other studies [19,20], yet this diversity tended to decrease over time probably because of natural selection [35][36][37]. The regenerating Scots pine seedlings retained the same (Swedish study by Yazdani et al [30]) or a slightly increased level of expected heterozygosity (Polish study by Nowakowska et al [31]) as compared to maternal trees.…”
Section: Discussionmentioning
confidence: 52%
“…The spatial distribution of genetic diversity in forest stands influences subsequent mating, as the majority (approximately 70%) of seeds are produced by trees whose flowers have been fertilised by pollen from neighbouring trees growing within a radius of 15 m around the maternal tree [33,34]. Temporal distribution of genetic diversity in forest stands reflects ongoing natural selection and is normally reduced along with increasing stand age [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast microsatellites (cpSSRs), alongside other markers such as nuclear SSRs, RFLPs, mitochondrial markers and allozymes, have for many years been the basic and universal tools used to characterize tree genetic resources (Vendramin et al 1996;Ribeiro et al 2002;Navascués et al 2006), including the Scots pine (Provan et al 1998;Dzialuk and Burczyk 2002;Wojnicka-Półtorak et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The study mentioned above shows a variation between natural populations in Asia and Eastern Europe of 2.1% [21], and slightly lower results were found for populations from Estonia [22]. In Poland, a study of cpDNA diversity between age classes of stocks was conducted [23], which showed a similar level of diversity as between different populations. Wojnicka-Póltorak et al [23] point to the transfer of foreign pollen to the parent population as one of the reasons for the detected differentiation.…”
Section: Introductionmentioning
confidence: 88%